EFEKTIFITAS METODE MUROTTAL DALAM MENGHAFAL AL-QUR’AN BAGI ORANG DEWASA DI PROGRAM TAHFIDZ PRIVAT - Moch Rohman Romadhon; Dahliana, Yeti (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research analyzes the effectiveness of the murottal method in enhancing both the speed and long-term retention of Quranic memorization among adult participants in private tahfidz programs. Utilizing a quasi-experimental pretest-posttest control group design, the study involved eight adult learners aged 26–35, randomly assigned to either an experimental group employing the murottal method with structured audio listening or a control group using traditional manual techniques. Memorization was assessed through rigorous oral testing, evaluating fluency, tajwid accuracy, and makhraj. The findings reveal a marked superiority of the murottal approach: the experimental group successfully memorized 100% of the target verses (20 verses) and retained 92.5% of the material after one month. In stark contrast, the control group achieved only 60% memorization with a retention rate of 45.83%. Statistical analysis confirmed these differences were significant. These results demonstrate that the murottal method, which actively engages auditory memory and utilizes melodic reinforcement, is a substantially more effective strategy for adult memorization. Therefore, the study strongly advocates for the formal integration of this method into tahfidz curricula to improve pedagogical efficiency and learning outcomes for adult students.